Multicomponent-assembled nanodiamond hybrids for targeted and imaging guided triple-negative breast cancer therapy via a ternary collaborative strategy. (22nd April 2021) - Cui, Xinyue; Deng, Xiongwei; Liang, Zhaoyuan; Lu, Jianqing; Shao, Leihou; Wang, Xuan; Jia, Fan; Pan, Zian; Hu, Qin; Xiao, Xiangqian; Wu, Yan; Sheng, Wang
Abstract : A multicomponent-assembled nanodiamond hybrid theranostic nanoplatform exhibits Cur/PDT/PTT ternary collaborative triple-negative breast cancer therapy via curcumin and IR780 co-delivery. Abstract : Uniting combinational strategies has been confirmed to be a robust choice for high-performance cancer treatment due to their abilities to overcome tumor heterogeneity and complexity. However, the development of a simple, effective, and multifunctional theranostics nanoplatform still remains a challenge. In this study, we integrated multicomponent hyaluronic acid (HA), protamine (PS), nanodiamonds (NDs), curcumin (Cur), and IR780 into a single nanoplatform (denoted as HPNDIC) based on the combination of hydrophobic and electrostatic noncovalent interactions for dual-modal fluorescence/photoacoustic imaging guided ternary collaborative Cur/photothermal/photodynamic combination therapy of triple-negative breast cancer (TNBC). A two-step coordination assembly strategy was utilized to realize this purpose. In the first step, PS was utilized to modify the NDs clusters to form positively charged PS@NDs (PND) and the simultaneous encapsulation of the natural small-molecule drug Cur and the photosensitive small-molecule IR780 (PNDIC). Second, HA was adsorbed onto the outer surface of the PNDIC through charge complexation for endowing a tumor-targeting ability (HPNDIC). The resulting HPNDIC had a uniform size, high drug-loading ability, and excellent colloidal stability. It was found that under the near-infrared irradiation condition, IR780 could be triggered to exhibit both PTT/PDT dual-pattern therapy effects, leading to an enhanced therapy efficiency of Cur both in vitro and in vivo with good biocompatibility. Due to the intrinsic imaging property of IR780, the biodistribution and accumulation behavior of HPNDIC in vivo could be monitored by dual-modal fluorescence/photoacoustic imaging. Taken together, our current work demonstrated the assembly of a NDs-based multicomponent theranostic platform for dual-modal fluorescence/photoacoustic imaging guided triple-collaborative Cur/photothermal/photodynamic against TNBC.